Transformations in Learning Spaces -Impact of Mobile Technologies on Student Learning - Rana, Lata (Journal of Education and Training, 2024)
As a result of innovation in technology, social media and mobile devices have changed the face of teaching and learning. The use of tools such as Facebook, Twitter, Blogs and Short Messaging Services (SMS) are continuing to grow with informal learning taking place outside formal educational settings. This paper draws on research conducted at a private tertiary institute and presents findings from the study. The focus of this study was to determine the learning that occurs through informal learning networks and how these support and enhance learning and wellbeing, particularly amongst international students. The research considers the implications of how teaching and learning are impacted by social and informal networking in the digital world.